Phase II Study of 5-Fluorouracil, Oxaliplatin plus Dasatinib (FOLFOX-D) in First-Line Metastatic Pancreatic Adenocarcinoma. (23rd June 2021) - George, Thomas J.; Ali, Azka; Wang, Yu; Lee, Ji-Hyun; Ivey, Alison M.; DeRemer, David; Daily, Karen C.; Allegra, Carmen J.; Hughes, Steven J.; Fan, Z. Hugh; Cameron, Miles E.; Judge, Andrew R.; et al.
Abstract: Lessons Learned : Preclinical studies have demonstrated that Src inhibition through dasatinib synergistically enhances the antitumor effects of oxaliplatin. In this phase II, single-arm study, FOLFOX with dasatinib in previously untreated patients with mPC only showed only modest clinical activity, with a progressive-free survival of 4 months and overall survival of 10.6 months. Continued investigation is ongoing to better understand the role of Src inhibition with concurrent 5-fluorouracil and oxaliplatin in a subset of exceptional responders. Background: Src tyrosine kinase activity is overexpressed in many human cancers, including metastatic pancreatic cancer (mPC). Dasatinib is a potent inhibitor of Src family of tyrosine kinases. This study was designed to investigate whether dasatinib can synergistically enhance antitumor effects of FOLFOX regimen (FOLFOX-D). Methods: In this single-arm, phase II study, previously untreated patients received dasatinib 150 mg oral daily on days 1–14, oxaliplatin 85 mg/m 2 intravenous (IV) on day 1 every 14 days, leucovorin (LV) 400 mg/m 2 IV on day 1 every 14 days, 5-fluorouracil (5-FU) bolus 400 mg/m 2 on day 1 every 14 days, and 5-FU continuous infusion 2, 400 mg/m 2 on day 1 every 14 days. Primary endpoint was progression-free survival (PFS) with preplanned comparison to historical controls. Results: Forty-four patients enrolled with an estimated median PFS of 4.0 (95% confidence interval [CI], 2.3–8.5) months and overall survival (OS) of 10.6 (95% CI, 6.9–12.7) months. Overall response rate (ORR) was 22.7% ( n = 10): one patient (2.3%) with complete response (CR) and nine patients (20.5%) with partial response (PR). Fifteen patients (34.1%) had stable disease (SD). Nausea was the most common adverse event (AE) seen in 35 patients (79.5%). Conclusion: The addition of dasatinib did not appear to add incremental clinical benefit to FOLFOX in untreated patients with mPC.